The First Live Birth in Lithuania After Application of Preimplantation Genetic Testing - Gudlevičienė, Živilė; Baušytė, Raminta; Dagytė, Evelina; Balkelienė, Danutė; Utkus, Algirdas; Ramašauskaitė, Diana (Acta medica Lituanica, 2020)
Background. Preimplantation genetic testing (PGT) is a genetic testing procedure that is performed before the implantation of embryos for the identification of genetic abnormalities. It is commonly performed when one or both expecting parents have such abnormalities and are at a high risk of passing them to their offspring. The aim of this case report is to describe the first successful IVF/ICSI/PGT procedure in Lithuania. Case report. A 27-year-old woman and a 31-year-old man, a married couple, were referred to VUHSK Santaros Fertility Center after trying to conceive for 4 years. In a previous relationship, the woman got pregnant spontaneously and decided to terminate the pregnancy. The husband does not have any children. During the medical examination, the transvaginal ultrasound revealed a low antral follicle count and low anti-Müllerian hormone level for the woman. Semen analysis for the male patient showed severe oligoastenospermia, which confirmed the previous abnormal spermogram results. Chromosome analysis revealed normal karyotype for the woman (46,XX) and Robertsonian translocation for the husband (45,XY,der(13;14)(q10;q10)). After the interdisciplinary medical team counselling, an ICSI with PGT-SR was suggested for the couple. The woman underwent controlled ovarian hyperstimulation with GnRH antagonist protocol for 11 days. Only one embryo with no unbalanced rearrangements was identified and transferred to the woman. On the 14th day post oocyte retrieval, the first serum β-hCG result was received – 39.5 mIU/ml, and the normal gestational sac at 5 weeks and 3 days was confirmed by ultrasound examination. Conclusion: the first successful pregnancy was achieved in Lithuania and the first IVF/ICSI/PGT-SR newborn in Lithuania was born in 2019 – a vaginal birth of a healthy girl with gestational age of 38 weeks and 4 days and a weight of 2820 g; the Apgar score was 10/10. The IVF/ICSI/PGT procedure was successfully implemented by the multidisciplinary team in VUHSK.